"DELAYED DIAGNOSIS OF PEDIATRIC TAKAYASU ARTERITIS: A CASE OF MULTISYSTEM PRESENTATION OVER EIGHT YEARS" (The Research of Medical Science Review, 2025)
Takayasu's arteritis (TA) is a rare type of vasculitis, a group of disorders that causes blood vessel inflammation. In Takayasu's arteritis, the inflammation damages the large artery that carries blood from your heart to the rest of your body (aorta) and its main branches. In this case, a 6-yearold girl who repetitively presented to OPD with complaints of abdominal pain and fever, each time was misdiagnosed for eight years. She underwent extensive investigations but all of them went uneventful. The unusualness here lies in repetitive presentation with abdominal symptoms (pain/distension that were not explained). Afterwards she underwent aortogram that revealed some significant findings including stenosis of both subclavian arteries, tapering of thoracic aorta and subtotal occlusion of abdominal aorta. She met EULAR/PRES criterion for pediatric Takayasu Arteritis and was diagnosed henceforth. This case highlights that Takayasu Arteritis can present with abdominal distension and generalized symptoms, particularly due to unusual findings like subtotal occlusion of the abdominal aorta. Given that Takayasu arteritis is rare in children, reporting such cases aids pediatricians and rheumatologists in recognizing this condition earlier and improving treatment outcome.